2018
DOI: 10.1017/s1751731118000095
|View full text |Cite
|
Sign up to set email alerts
|

The impact of floor type on lameness and hoof health of dairy origin bulls

Abstract: This study aimed to evaluate the effect of using different floor types to accommodate growing and finishing beef cattle on lameness. In all, 80 dairy origin bulls were blocked according to live weight and breed into 20 groups, and randomly allocated within groups to one of four treatments. The floor types studied were fully slatted flooring throughout the entire experimental period (CS); fully slatted flooring covered with rubber strips throughout the entire experimental period (RS); fully slatted flooring dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Murphy et al ( 85 ) reported that increased toe net growth does not adversely affect the walking ability. Despite the greater toe net growth in bulls accommodated on rubber flooring, there was no effect of floor type on locomotion score, suggesting that the increased toe net growth does not adversely affect the walking ability.…”
Section: Influence Of Feeding System On Beef and Carcass Propertiesmentioning
confidence: 99%
“…Murphy et al ( 85 ) reported that increased toe net growth does not adversely affect the walking ability. Despite the greater toe net growth in bulls accommodated on rubber flooring, there was no effect of floor type on locomotion score, suggesting that the increased toe net growth does not adversely affect the walking ability.…”
Section: Influence Of Feeding System On Beef and Carcass Propertiesmentioning
confidence: 99%
“…In addition, the impact of production system on animal health should also be considered. Long term housing cattle on slatted flooring may have a negative impact on hoof health [ 11 ], while autumn housing of cattle after grazing can be a high risk period for pneumonia [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the effects found in this study, long-term benefits may be expected, which are to be evaluated in further research. Prolonged use of softer barn floor types can reduce lameness in dairy cows, heifers, and dairy-origin beef cattle [21,22,23] (although such benefits are not always achieved [24]). Similar benefits could be gained from the prolonged use of artificial grass laneways.…”
Section: Discussionmentioning
confidence: 99%